2005
DOI: 10.1007/s11135-005-2177-z
|View full text |Cite
|
Sign up to set email alerts
|

On scales and decision-making based on arithmetic mean

Abstract: ordinal scales, grading scales, equivalent scales, arithmetic mean or average, grade or mark conversion, decision-making,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Given the ordinality characteristic of the educational grading scales, it is well known that arithmetic mean is not an appropriate statistic (Stevens, 1951(Stevens, , 1955Ieta, 2004). However, in our recent work (Ieta et al, 2004) we have demonstrated a theorem for the selection of equivalent ordinal scales. Comparison of arithmetic mean (ranks) originating on different ordinal scales is appropriate for such scales.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Given the ordinality characteristic of the educational grading scales, it is well known that arithmetic mean is not an appropriate statistic (Stevens, 1951(Stevens, , 1955Ieta, 2004). However, in our recent work (Ieta et al, 2004) we have demonstrated a theorem for the selection of equivalent ordinal scales. Comparison of arithmetic mean (ranks) originating on different ordinal scales is appropriate for such scales.…”
Section: Introductionmentioning
confidence: 76%
“…Some brief remarks will be made regarding a possible application of arithmetic mean ranks, as defined and studied so far (Ieta et al, 2004), to a candidate selection process. A two-stage candidate selection process will be considered.…”
Section: Selection Proceduresmentioning
confidence: 99%
See 3 more Smart Citations